In Silico Analysis Effect of Potential Antidiabetic from Dandang Gendis Extract on Aldose Reductase, Glucokinase, and GSK3β for Type 2 Diabetes Mellitus - Safira Raissa Dwi Putri; Irda Bella; Siti Khaerunnisa; Nurlaili Susanti; Arifa Mustika (Universitas Airlangga, 2023)
Introduction: Diabetes mellitus is a metabolic disease characterized by hyperglycemia. Various epidemiological studies have shown a trend of increasing incidence and prevalence of diabetes mellitus in various parts of the world. Therefore, diabetes mellitus is currently a global health threat. Dandang gendis (Clinacanthus nutans) is a widely used plant as a traditional herbal treatment in Indonesia, and it has been proven that the ethanol extract of dandang gendis leaves shows an antidiabetic effect. This research aims to determine the compatibility among the flavonoid compounds in C. nutans with Aldose reductase, glucokinase, and GSK3β target drugs for type 2 diabetes mellitus using in silico method.Methods: 45 compounds were obtained from multiple sources. The screening method used Lipinski’s rule of five and Pyrx until 8 compounds were selected. Avogadro, AutoDock 4.2, and Biovia Discovery Studio 2016 were used for molecular docking and visualization analysis.Results: Molecular docking results demonstrate that the ligand-protein interaction’s binding energy was -7.31 to 35.25 kcal/mol for 1AH3, -7.55 to 0.15 kcal/mol for 1V4S, and -7.99 to -2.85 kcal/mol for 3D0E.Conclusion: We can conclude that flavonoid compounds Apigenin, Vitexin, 3,3-di-O-Methylellagic Acid, and Clinacoside C show a high binding affinity with Aldose Reductase, Glucokinase, and GSK3β proteins and have the potential to be oral antidiabetic drug compounds for Diabetes Mellitus. However, its binding affinity has not been able to exceed that of the native ligand of the protein. Further research is needed to determine the significant efficacy and potential as an antidiabetic.